Theoretical and experimental analysis of the quasi-static and dynamic behaviour of the world's longest suspension footbridge in 2020. (15th February 2022) - Tadeu, António; Romero, António; Bandeira, Filipe; Pedro, Filipe; Dias, Sara; Serra, Miguel; Brett, Michael; Galvín, Pedro
Highlights: Static and dynamic responses by linear and nonlinear theoretical and numerical models. The dynamic behaviour of the bridge described from in and out of plane mode shapes. Seventeen modes are identified in this frequency range below 1 Hz. Computed results versus in-situ data recorded by GNNS antennas and accelerometers. Modal damping ratios, identified based on full-scale experimental data, are 0.3–2%. Abstract: This work validates the simplified theoretical, analytical and numerical models used in the preliminary design stage of the 516 Arouca footbridge over the River Paiva (Portugal), the world's longest suspension footbridge. The models were used to define the configuration of the bridge under static loading and the eigenfrequencies excited under dynamic loading. The three-dimensional finite element model used in the detailed design of the bridge is briefly described. The paper also presents in situ experimental results. Tests were performed to study the static and dynamic behaviour of the footbridge under service loads and to assess the analytical/numerical modelling assumptions. The structure was subjected to loads generated by the wind and by a group of people crossing the bridge. Global Navigation Satellite System (GNSS) antennas were used to record the displacements of the bridge under quasi-static loadings caused by the people crossing the bridge at a slow pace. The data recorded by a set of seismometers allowed us to identify the natural frequencies and modes of vibration. The agreement between all the analytical/numerical solutions and the experimental data was found to be very good. The data recorded also allowed one to evaluate the damping coefficients of the bridge for the different vibration modes, something that is very difficult to predict in the design stage.